Characterization Of Banana (Musa Acuminata × Balbisiana Cv. Awak) Pseudo-Stem Flour And Its Potential In The Development Of Novel Fibre-Rich Bread - Ho, Lee Hoon (2013)
The physico-chemical and functional properties of banana pseudo-stem flour (BPF) was compared with the commercial wheat flour (CWF). Unbleached and bleached cellulose were prepared from BPF. Various flour blends were formulated; CWF (FCWF), FCWF was substituted with 10% BPF (F10BPF) and F10BPF with added 0.8% w/ w (flour weight basis) xanthan gum (XG) or sodium carboxymethyl cellulose (Na CMC) (F10BPFXG or F10BPFCMC, respectively). The formulated flour blends were subjected to the mixing, pasting, and thermal profiles analyses. Novel composite breads by partially substituting BPF for control CWF bread (BCtr) at 10% level (B10BPF) and B10BPF added with 0.8% w/ w of XG or Na CMC (B10BPFXG or B10BPFCMC, respectively) were prepared and evaluated for the physico-chemical, nutritional and sensory. The proximate contents (fat, ash, crude fibre and carbohydrate), macro and micro elements, total dietary fibre (TDF), insoluble dietary fibre (IDF), soluble dietary fibre (SDF), total sugars, pentosans, total phenolics, antioxidants activity, pH, ⁰Brix, titratable acidity, water and oil holding capacities were significantly (p< 0.05) higher in BPF than in CWF. BPF had low bulk density, water activity (aw) and lightness value. Low yield and high crystallinity were obtained from bleached cellulose as confirmed by the fourier transform infrared spectroscopy and x-ray diffraction results. All composite flour blends showed significantly (p< 0.05) high water absorption and mixing tolerance index with decreased in gelatinization enthalpy change (ΔHg), breakdown, final viscosity and setback values.